Os golpes de estado na Guiné Bissau: o cotidiano do poder no contexto da diversidade étnica e da construção nacional - Bijagó, Vagner Gomes (2011)
This Dissertation analyzes the coups and the daily life of power in Guinea-Bissau between 1980 and 2003, a period which marks the first coup since independence and the first coup to a civilian president not coming from the summit African Party for Independence of Guinea and Cape Vert (PAIGC). Based on qualitative research literature, historical and documentary research contextualizes the country traversed by the different periods and reflects on the logic operating at different times of strikes, as well as the challenges to build the nation state in a context marked by extraordinary ethnic diversity. From this frame of reference, the essay analyzes the causes and consequences of the culture of violence in period of economic openness and democratic, as well as advances and retreats in the ordering of social development from traditional and modern elements.